Doktrina in metode socialnega dela na področju podpore žrtvam spolnih zlorab v katoliški cerkvi - Zaviršek, Darja (Socialno delo, 2016)
Sexual abuses in the Catholic Church are a global problem, but the victims have only started to report it in greater numbers in the last 15 years. In Slovenia, a more intensive disclosure of sexual abuses among priests has been noted after 2000. The article presents the chronology of reported suspicions and legal procedures against suspects, of their charges and punishments. In revising the discussion about sexual abuses in the Catholic Church, the problem of non-reporting and non-action of the Roman Catholic Church comes to the fore as something to do with the Concordat between the Roman Catholic Church and the Republic of Slovenia. One of the main reasons for sexual abuses in the Church seems to be the traditional Catholic culture, based on the Church doctrine, that presents children as adults% property, and on the historic interest of the Church in controlling women's sexuality. The problems of victims' silence, the disclosure, and the ambivalent position of parents are presented in the article as well as basic theories of social work in dealing with survivors, such as advocacy, recovery, resilience, and sensibilisation for the child's perspective. These theories are the conceptual framework for methods of work with victims and their parents and for the prevention work with children in general and with community. Several reports are presented in the article, including an original report on sexual harassment by a priest. One of the key tasks for social workers in social care system is encouraging victims to speak out and supporting them during the recovery process.
Keywords: duhovniki; priest; sexual harassment; spolno nadlegovanje; silence; molk; okrevanje; recovery; zagovorništvo; advocacy; social care; socialno varstvo